2023
DOI: 10.1038/s41467-023-39850-2
|View full text |Cite
|
Sign up to set email alerts
|

Implant-to-implant wireless networking with metamaterial textiles

Abstract: Implanted bioelectronic devices can form distributed networks capable of sensing health conditions and delivering therapy throughout the body. Current clinically-used approaches for wireless communication, however, do not support direct networking between implants because of signal losses from absorption and reflection by the body. As a result, existing examples of such networks rely on an external relay device that needs to be periodically recharged and constitutes a single point of failure. Here, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Simultaneously, ensuring reliable data communication in a body-implanted sensor demands advancements in miniaturization and wireless technology, underpinned by secure, efficient data transmission protocols. Biodegradable sensors leverage thin wires or wireless data transmitters based on resonant inductive coupling, emphasizing the need for materials and designs that support short-distance, high-fidelity data communication without compromising biocompatibility or increasing infection risks [267]. Materials selection for these sensors is critical, with a focus on biodegradability, compatibility with human tissues, and functionality.…”
Section: Integrated Design Considerationsmentioning
confidence: 99%
“…Simultaneously, ensuring reliable data communication in a body-implanted sensor demands advancements in miniaturization and wireless technology, underpinned by secure, efficient data transmission protocols. Biodegradable sensors leverage thin wires or wireless data transmitters based on resonant inductive coupling, emphasizing the need for materials and designs that support short-distance, high-fidelity data communication without compromising biocompatibility or increasing infection risks [267]. Materials selection for these sensors is critical, with a focus on biodegradability, compatibility with human tissues, and functionality.…”
Section: Integrated Design Considerationsmentioning
confidence: 99%
“…Designing tunable metamaterial structures can also be a robust solution to this problem (Lee and Yoon 2020b ; Boardman et al 2011 ). In addition, while considering the IMDs, conformal metasurface can significantly improve the user-friendliness (Tian et al 2023 ; Hajiaghajani et al 2022 ).…”
Section: Challenges and Limitations Of Using Metamaterials Powering Imdsmentioning
confidence: 99%
“…Our approach uses metamaterial textiles-structured conductive fabrics engineered to have unique electromagnetic properties (30). While prior research has reported using such metamaterials to enhance wireless networking for wearables (26) and implantable devices (31), our current work demonstrates their capability to mediate near-field interactions between body tissues and wireless signals for highly sensitive and interference-immune sensing of vital signs. The results are thin, conformal sensors that can integrate with everyday passive surfaces to offer accurate and reliable detection of subtle physiological motions from different body regions without requiring active user participation (tables S1 and S2).…”
Section: Introductionmentioning
confidence: 96%